Multi-band whole-body diffusion-weighted imaging with inversion recovery fat saturation: Effects of respiratory compensation. (2021) - Larsen, Solveig Kärk Abildtrup; Sivesgaard, Kim; Pedersen, Erik Morre
Highlights: MB reduces DWIBS scan time which can be reinvested in respiratory compensation. MB enables respiratory trigger in DWIBS while maintaining low acquisition time. MB enables very fast DWIBS sequences that still produce acceptable image quality. Abstract: Purpose: To prospectively compare artefacts and image quality in testicular stage I cancer patients using different combinations of breathing schemes and Multi-band (MB) in whole-body DWIBS at 1.5 T. Diffusion-Weighted whole-body Imaging with Background body signal Suppression (DWIBS) using inversion recovery (IR) fat saturation is a cornerstone in oncologic whole-body MRI, but implementation is restrained by long acquisition times. The new Multi-Band (MB) technique reduces scan time which can be reinvested in respiratory compensation. Methods: Thirty testicular cancer stage I patients were included. Three variations of whole-body DWIBS were tested: Standard free Breathing (FB)-DWIBS, FB-MB-DWIBS and Respiratory triggered (RT)-MB-DWIBS. Artefacts and image quality of b = 800 s/mm 2 images were evaluated using a Likert scale. No pathology was revealed. SNR was calculated in a healthy volunteer. Results: RT-MB-DWIBS was rated significantly better than FB-DWIBS in the thorax (p < 0.001) and abdomen (p < 0.001), but not in the pelvis (p = 0.569). FB-MB-DWIBS was ranked significantly lower than both FB-DWIBS (p < 0.001) and RT-MB-DWIBS (p < 0.001) at all locations. However, FB-MB-DWIBS was scanned in half the time without being less than "satisfactory". Few artefacts were encountered. SNR was similar for low-intensity tissues, but the SNR in high-intensity and respiratory-prone tissue (spleen) was slightly lower for FB-DWIBS than the other sequences. Conclusion: Images produced by the sequences were similar. MB enables the use of respiratory trigger or can be used to produce very fast free-breathing DWI with acceptable image quality.